Regressive or Progressive? : The Effect of Tobacco Taxes in Ukraine - Fuchs, Alan; Meneses, Francisco (World Bank, Washington, DC, 2017)
Tobacco taxes are usually considered regressive as the poorest individuals allocate larger shares of their budget towards the purchase of tobacco related products. However, because these taxes also discourage tobacco use, some of the most adverse effects and their economic costs are reduced, including lower life expectancy at birth, higher medical expenses, increased years of disability among smokers, and the effects of secondhand smoke. This paper projects the effects of an increase in the tobacco tax on household welfare in Ukraine. It considers three price-elasticity scenarios among income deciles of the population. Results show that although tobacco taxes are often criticized for being regressive in the short-run, a more comprehensive scenario that includes medical expenses and working years, the benefits of tobacco taxes far exceed the increase in tax liability, benefitting in large measure lower income households. Our results also indicate that lower health expenditure seems to be the main driver because of the reduction in tobacco-related diseases that require expensive treatments. Tobacco taxes are also associated with positive distributional effects related to the higher long-term price elasticities of tobacco consumption.